Forensic Accounting and Information Systems Auditing: A Coordinated Approach to Fraud Investigation in Banks (gjstudies, 2021)
This research examines the coordinated application of forensic accounting techniques and Information Systems auditing in bank fraud investigations, with particular focus on uncovering concealed financial misstatements and sophisticated fraudschemes. Through comprehensive analysis of 132 documented bank fraud casesacross North America, Europe, and Asia from 2018 to 2021, this study develops anintegrated investigation framework that leverages the complementary strengths ofboth disciplines. The research introduces a novel Coordinated Fraud InvestigationIndex (CFII) that quantifies investigation effectiveness across financial analysis, digital evidence collection, and investigative integration dimensions. Empirical resultsdemonstrate that coordinated investigations achieve 67% higher fraud detectionrates and 54% faster case resolution compared to isolated disciplinary approaches.The study reveals that concealed financial misstatements account for 42% of sophisticated bank frauds, with digital evidence from IS audits proving critical in 78%of successful investigations. Findings indicate that successful coordination requiresstructured collaboration protocols, shared investigative methodologies, and integrated reporting frameworks. This research contributes both theoretical advancements in fraud investigation methodology and practical implementation guidelinesfor banking institutions seeking to enhance their fraud detection and investigationcapabilities through disciplinary integration.